ABSENCES IN PREPARATORY PHASE OF ROAD OVERSIZE TRANSPORT ORGANISATION IN CZECH REPUBLIC (Perner's Contacts, 2011)
The article analyzed the actualy missing tools in the technological process of road oversize transport, especially in the preparatory phase. To individual absebces are got in solutions.The Author has also dealt with a problem involving thespecial transportation during crisis situation.
Keywords: crisis situation; oversize transport; permit; transport line